Secondary battery electrolyte additive and application
By using electrolyte additives with specific structures, the problems of low conductivity and insufficient high-temperature cycle performance of the passivation film on the surface of secondary battery electrodes were solved, thereby improving the high-temperature stability and cycle performance of the battery.
Patent Information
- Application Number
- CN202411050807.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-01
- Publication Date
- 2026-02-03
AI Technical Summary
The passivation film on the electrode surface of existing secondary batteries has low ionic conductivity, is easily decomposed, and has insufficient high-temperature cycle performance. Existing electrolyte additives cannot effectively improve the high-temperature storage and cycle performance of batteries.
An electrolyte additive with a specific structure is used. This additive contains a cyclic structure with sulfate, sulfite, or carbonate groups at both ends, linked by a ketone carbonyl group in the middle. This compound can coordinate with metal ions in the electrolyte salt and undergo an electrochemical reaction on the electrode surface to form an organic thin film with good stability, high structural strength, and good ion permeability.
It improves the high-temperature storage and high-temperature cycling performance of secondary batteries, and enhances the stability and ion conduction capacity of the batteries.
Smart Images

Figure CN121460705A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of secondary batteries, in particular to an electrolyte additive and application. BACKGROUND
[0002] With the development of science and technology, the improvement of human life quality, and the increasing emphasis on green environmental protection, the application range of secondary batteries is becoming more and more extensive. For example, lithium ion batteries have been widely applied in 3C products, electric vehicles and hybrid vehicles and other equipment due to their high energy density and power density, good safety characteristics, excellent cycle performance and wide temperature application research progress, such as higher energy density, excellent cycle performance and good safety.
[0003] A secondary battery is composed of a positive electrode, a negative electrode, a separator and an electrolyte, and each component will greatly affect the performance. The solid electrolyte interface film (SEI) on the surface of the electrode has been widely studied and discussed. The performance of the SEI layer film between the electrode material and the electrolyte depends on its ionic conductivity, ion transfer number and stability to the electrolyte, etc. However, the inventors found that the existing electrode sheet still has problems such as low ionic conductivity of the surface passivation film (i.e. the above-mentioned SEI), easy decomposition, insufficient high-temperature cycle performance, etc., and a suitable electrolyte additive can help solve such problems.
[0004] Therefore, how to develop a secondary battery electrolyte additive with film-forming properties and good ionic conductivity, stability and cycle performance is a problem to be solved. SUMMARY
[0005] Therefore, one object of the present application is to provide an electrolyte additive. The electrolyte additive contains a compound having a structure shown in Formula 1, i.e. a cyclic structure containing a sulfate group, a sulfite group or a carbonate group at both ends connected together through a cyclic structure containing a ketone carbonyl group. The ketone carbonyl group can coordinate with metal ions (e.g. lithium ions) in the electrolyte salt, which is beneficial to the movement of the additive to the electrode surface with the current and the electrochemical reaction on the electrode surface. On the one hand, the ester group-containing ring can be opened to react with the electrolyte salt (e.g. lithium salt) in the electrolyte to form an organic electrolyte salt (e.g. organic lithium salt); on the other hand, the ring-opening of the cyclic ketone structure can cross-link with organic matter in the battery or itself to form a double electrolyte salt (e.g. lithium salt) organic film with good stability, high structural strength and good ion permeability, thereby improving the high-temperature storage and high-temperature cycle performance of the battery.
[0006] Another object of the present application is to provide an electrolyte.
[0007] Still another object of the present application is to provide a secondary battery.
[0008] To achieve the above object, the first aspect of the present application provides an electrolyte additive, comprising a compound having a structure shown in Formula 1:
[0009]
[0010] wherein X, Y are each independently selected from R1, R2 are each independently selected from a single bond, substituted or unsubstituted -CH2-, substituted or unsubstituted -CH2-CH2-.
[0011] In some embodiments, the substituent in the substituted or unsubstituted -CH2-, substituted or unsubstituted -CH2-CH2- is halogen.
[0012] In some embodiments, the compound having a structure shown in Formula 1 comprises at least one of Compound 1 to Compound 10:
[0013]
[0014] The second aspect of the present application provides an electrolyte, comprising a non-aqueous organic solvent, an electrolyte salt and the electrolyte additive described in the present application.
[0015] In some embodiments, the mass content of the compound having a structure shown in Formula 1 in the electrolyte is 0.05-10%, preferably 0.1-5%.
[0016] In some embodiments, the non-aqueous organic solvent comprises at least one of an ether solvent, a nitrile solvent, a carbonate solvent, a carboxylate solvent and a sulfone solvent.
[0017] In some embodiments, the electrolyte salt comprises at least one of a lithium salt, a sodium salt, a potassium salt, a magnesium salt, a zinc salt and an aluminum salt, preferably a lithium salt or a sodium salt.
[0018] In some embodiments, the lithium salt comprises at least one of LiPF6, LiBOB, LiDFOB, LiPO2F2, LiBF4, LiSbF6, LiAsF6, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiC(SO2CF3)3, LiN(SO2F)2, LiClO4, LiAlCl4, LiCF3SO3, Li2B 10 Cl 10 , a lithium salt of a lower aliphatic carboxylic acid.
[0019] In some embodiments, when the electrolyte salt is a lithium salt, the concentration of the lithium salt in the electrolyte is 0.1-8 mol / L.
[0020] In some embodiments, the sodium salt comprises at least one of sodium perchlorate, sodium hexafluorophosphate, sodium tetrafluoroborate, sodium bisfluorosulfonimide, sodium trifluoromethylsulfonate, sodium bis-trifluoromethylsulfonimide.
[0021] In some embodiments, when the electrolyte salt is a sodium salt, and the concentration of the sodium salt in the electrolyte is 0.1-2 mol / L.
[0022] In some embodiments, the electrolyte further comprises an auxiliary additive selected from at least one of a cyclic carbonate compound, a cyclic sulfate compound, a sulfonic acid lactone compound, a phosphate compound, a borate compound, and a nitrile compound.
[0023] In some embodiments, the cyclic carbonate compound is selected from at least one of vinylene carbonate, vinyl ethylene carbonate, methylene vinyl carbonate, fluoro vinyl carbonate, trifluoromethyl vinyl carbonate, bis-fluoro vinyl carbonate, or a compound having a structure shown in Formula 2.
[0024]
[0025] In Formula 2, R 21 , R 22 , R 23 , R 24 , R 25 , R 26 are each independently selected from one of a hydrogen atom, a halogen atom, and a C1-C5 group.
[0026] In some embodiments, the cyclic sulfate compound is selected from at least one of vinyl sulfate, 4-methyl vinyl sulfate, propylene sulfate,
[0027] In some embodiments, the sulfonic acid lactone compound is selected from at least one of 1,3-propane sulfonic acid lactone, 1,4-butane sulfonic acid lactone, propylene-1,3-sulfonic acid lactone,
[0028] In some embodiments, the phosphate compound comprises a saturated phosphate compound and an unsaturated phosphate compound, wherein the saturated phosphate compound comprises tris(trimethylsilyl) phosphate, and the unsaturated phosphate compound comprises a compound having a structure shown in Formula 3.
[0029]
[0030] In Formula 3, R 31 , R 32 , R 32 each independently selected from a C1-C5 saturated hydrocarbon group, a C1-C5 unsaturated hydrocarbon group, a C1-C5 halogenated hydrocarbon group, or -Si(C m H 2m+1 )3, m is a natural number from 1 to 3, and the R 31 , the R 32 , the R 33 at least one of which is an unsaturated hydrocarbon group.
[0031] In some embodiments, the borate compound comprises at least one of tris(trimethylsilyl) borate, tris(triethylsilyl) borate.
[0032] In some embodiments, the nitrile compound comprises at least one of butanedinitrile, pentanedinitrile, ethylene glycol bis(propionitrile) ether, hexanetristitnile, hexanedinitrile, heptanedinitrile, octanedinitrile, nonanedinitrile, decanedinitrile.
[0033] A third aspect of the present application provides a secondary battery comprising a positive electrode, a negative electrode, and an electrolyte, wherein the electrolyte is the electrolyte described in the present application.
[0034] In some embodiments, the secondary battery is selected from a lithium metal battery, a lithium ion battery, a lithium-sulfur battery, a sodium ion battery, a magnesium ion battery, a potassium ion battery, a zinc ion battery, or an aluminum-lithium battery.
[0035] In some embodiments, the secondary battery is a lithium ion battery, and the positive electrode active material of the secondary battery is selected from at least one of a lithium-containing sulfide, a lithium-containing selenide, a lithium-containing halide, LiFe 1-x’ M’ x’ PO4, LiMn 2-y’ M y’ O4, and LiNi x Co y Mn z M 1-x-y-z O2, wherein M’ is selected from at least one of Mn, Mg, Co, Ni, Cu, Zn, Al, Sn, B, Ga, Cr, Sr, V, or Ti, M is selected from at least one of Fe, Co, Ni, Mn, Mg, Cu, Zn, Al, Sn, B, Ga, Cr, Sr, V, or Ti, and 0≤x’<1, 0≤y’≤1, 0≤y≤1, 0≤x≤1, 0≤z≤1, x+y+z≤1.
[0036] In other embodiments, the secondary battery is a sodium ion battery, and the positive electrode active material is selected from at least one of a sodium-containing transition metal oxide, a sodium-containing Prussian blue material, a sodium-containing phosphate, a sodium-containing sulfate, a sodium-containing titanate.
[0037] The electrolyte additive described in the present application can at least bring the following beneficial effects:
[0038] The electrolyte additive contains a compound having the structure shown in Formula 1, i.e., a cyclic structure containing sulfate groups, sulfite groups or carbonate groups at both ends connected together through a cyclic structure containing a ketone carbonyl group, wherein the ketone carbonyl group can coordinate with metal ions (e.g., lithium ions) in electrolyte salts, facilitating the movement of the additive to the electrode surface with the current and the electrochemical reaction on the electrode surface; at the same time, the cyclic structure is opened ring during the electrochemical reaction, and it is empirically speculated that the cyclic sulfate, cyclic sulfite and cyclic carbonate are reacted with electrolyte salts (e.g., lithium salts) in the electrolyte to form organic electrolyte salts (e.g., organic lithium salts); at the same time, the cyclic ketone structure is opened ring and cross-linked with organic matters in the battery or itself to form a double electrolyte salt (e.g., lithium salt) organic film with good stability, high structural strength and good ion permeability, thereby improving the high-temperature storage and high-temperature cycle performance of the battery.
[0039] Additional aspects and advantages of the present application will be in part apparent and in part pointed out hereinafter in the description. DETAILED DESCRIPTION
[0040] The embodiments of the present application are described in detail below, which are exemplary and intended to explain the present application, and cannot be understood as a limitation of the present application.
[0041] In the present application, the disclosure of numerical ranges includes all values and further subdivided range disclosures within the entire range, including the endpoints and subranges given to these ranges.
[0042] In the present application, the raw materials, equipment, etc. involved, such as without special instructions, are raw materials, equipment that can be made by commercial means or known methods; the methods involved, such as without special instructions, are conventional methods.
[0043] <Electrolyte additive>
[0044] The electrolyte additive of the embodiments of the present application includes a compound having the structure shown in Formula 1:
[0045]
[0046] wherein X, Y are each independently selected from R1, R2 are each independently selected from a single bond, substituted or unsubstituted -CH2-, substituted or unsubstituted -CH2-CH2-.
[0047] In the embodiments of the present application, the term "substituted" means that the hydrogen in the structure is replaced by a substituent (e.g., halogen).
[0048] In some embodiments, each of the substituents in the substituted -CH2-, the substituted -CH2-CH2- is halogen.
[0049] In some embodiments, the term "halogen" refers to F, Cl, Br, or I.
[0050] In some embodiments, the compound of the structure of Formula 1 includes at least one of Compound 1 to Compound 10:
[0051]
[0052] The preparation method of the above-mentioned compound can be known by those skilled in the art according to the common knowledge in the field of chemical synthesis, based on the knowledge of the structural formula of the compound shown in Formula 1. For example:
[0053] Compound 1 can be prepared by the following method: aldol condensation of 1,4-cyclohexanedione with 4-6 equivalents of formaldehyde aqueous solution in the presence of 1-10 wt% (e.g., 5.5 wt%, etc.) calcium oxide at 30-80°C (e.g., 55°C, etc.) to prepare tetrahydroxymethylcyclohexanedione, then reaction of tetrahydroxycyclohexanedione with 2-3 equivalents (e.g., 2.5 equivalents, etc.) of dichlorosulfoxide at 30-80°C (e.g., 55°C, etc.) to prepare the sulfite, then oxidation of 2-3 equivalents (e.g., 2.5 equivalents, etc.) of hydrogen peroxide (e.g., hydrogen peroxide with a mass content of 20%) in the presence of 0.1-1 wt% phosphotungstic acid to obtain crude Compound 1, and recrystallization to obtain Compound 1.
[0054] As a non-limiting enumeration, Compound 2 can be prepared by the following method: aldol condensation of 1,4-cyclohexanedione with 4-6 equivalents (e.g., 5 equivalents, etc.) of formaldehyde aqueous solution in the presence of 1-10 wt% (e.g., 5.5 wt%, etc.) calcium oxide at 30-80°C (e.g., 55°C, etc.) to prepare tetrahydroxymethylcyclohexanedione, then preparation of crude Compound 2 from tetrahydroxycyclohexanedione and 2-10 equivalents (e.g., 6 equivalents, etc.) of dimethyl carbonate in the presence of 0.1-10 wt% (e.g., 5 wt%, etc.) potassium carbonate, and recrystallization to prepare Compound 2.
[0055] As a non-limiting example, compound 3 can be prepared by aldol condensation of 1,3-cyclopentanedione with 4-6 equivalents (e.g., 5 equivalents, etc.) of an aqueous formaldehyde solution in the presence of 1-10 wt% (e.g., 5.5 wt%, etc.) calcium oxide at 30-80 °C (e.g., 55 °C, etc.) to produce tetrahydroxymethyl cyclopentanedione, followed by reaction of the tetrahydroxycyclopentanedione with 2-3 equivalents (e.g., 2.5 equivalents, etc.) of dichlorosulfoxide at 30-80 °C (e.g., 55 °C, etc.) to produce a sulfite ester, followed by oxidation of the sulfite ester with 2-3 equivalents (e.g., 2.5 equivalents, etc.) of hydrogen peroxide (e.g., 20% hydrogen peroxide) in the presence of 0.1-1 wt% (e.g., 0.5 wt%, etc.) tungstophosphoric acid to produce crude compound 3, which is recrystallized to produce compound 3.
[0056] As a non-limiting example, compound 4 can be prepared by aldol condensation of 1,3-cyclopentanedione with 4-6 equivalents (e.g., 5 equivalents, etc.) of an aqueous formaldehyde solution in the presence of 1-10 wt% (e.g., 5.5 wt%, etc.) calcium oxide at 30-80 °C (e.g., 55 °C, etc.) to produce tetrahydroxymethyl cyclopentanedione, followed by reaction of the tetrahydroxycyclopentanedione with 2-3 equivalents (e.g., 2.5 equivalents, etc.) of dichlorosulfoxide at 30-80 °C (e.g., 55 °C, etc.) to produce crude compound 4, which is recrystallized to produce compound 4.
[0057] As a non-limiting example, compound 5 can be prepared by aldol condensation of 1,3-cyclobutanedione with 4-6 equivalents (e.g., 5 equivalents, etc.) of an aqueous formaldehyde solution in the presence of 1-10 wt% (e.g., 5.5 wt%, etc.) calcium oxide at 30-80 °C (e.g., 55 °C, etc.) to produce tetrahydroxymethyl cyclobutanedione, followed by reaction of the tetrahydroxycyclobutanedione with 2-3 equivalents (e.g., 2.5 equivalents, etc.) of dichlorosulfoxide at 30-80 °C (e.g., 55 °C, etc.) to produce a sulfite ester, followed by oxidation of the sulfite ester with 2-3 equivalents (e.g., 2.5 equivalents, etc.) of hydrogen peroxide (e.g., 20% hydrogen peroxide) in the presence of 0.1-1 wt% (e.g., 0.5 wt%, etc.) tungstophosphoric acid to produce crude compound 5, which is recrystallized to produce compound 5.
[0058] As a non-limiting example, compound 6 can be prepared by aldol condensation of 1,4-cyclohexanedione with 4-6 equivalents (e.g., 5 equivalents, etc.) of an aqueous formaldehyde solution in the presence of 1-10 wt% (e.g., 5.5 wt%, etc.) calcium oxide at 30-80 °C (e.g., 55 °C, etc.) to produce tetrahydroxymethyl cyclohexanedione, followed by reaction of the tetrahydroxycyclohexanedione with 2-3 equivalents (e.g., 2.5 equivalents, etc.) of dichlorosulfoxide at 30-80 °C (e.g., 55 °C, etc.) to produce a sulfite ester, followed by oxidation of the sulfite ester with 0.1-1 wt% (e.g., 0.5 wt%, etc.) phosphotungstic acid catalysis and 0.5-2 equivalents (e.g., 1.2 equivalents, etc.) of hydrogen peroxide (e.g., 20% hydrogen peroxide by mass) at 30-80 °C (e.g., 55 °C, etc.) to produce crude compound 6, which is recrystallized to produce compound 6.
[0059] As a non-limiting example, compound 7 can be prepared by aldol condensation of 1,3-cyclohexanedione with 4-6 equivalents (e.g., 5 equivalents, etc.) of an aqueous formaldehyde solution in the presence of 1-10 wt% (e.g., 5.5 wt%, etc.) calcium oxide at 30-80 °C (e.g., 55 °C, etc.) to produce tetrahydroxymethyl cyclohexanedione, followed by reaction of the tetrahydroxycyclohexanedione with 2-3 equivalents (e.g., 2.5 equivalents, etc.) of dichlorosulfoxide at 30-80 °C (e.g., 55 °C, etc.) to produce a sulfite ester, followed by oxidation of the sulfite ester with 0.1-1 wt% (e.g., 0.5 wt%, etc.) phosphotungstic acid catalysis and 2-3 equivalents (e.g., 2.5 equivalents, etc.) of hydrogen peroxide (e.g., 20% hydrogen peroxide by mass) at 30-80 °C (e.g., 55 °C, etc.) to produce crude compound 7, which is recrystallized to produce compound 7.
[0060] As a non-limiting example, compound 8 can be prepared by aldol condensation of 1,3-cyclohexanedione with 4-6 equivalents (e.g., 5 equivalents, etc.) of an aqueous formaldehyde solution in the presence of 1-10 wt% (e.g., 5.5 wt%, etc.) calcium oxide at 30-80 °C (e.g., 55 °C, etc.) to produce tetrahydroxymethyl cyclohexanedione, followed by reaction of the tetrahydroxycyclohexanedione with 2-10 equivalents (e.g., 6 equivalents, etc.) of dimethyl carbonate in the presence of 0.1-10 wt% (e.g., 5.5 wt%, etc.) potassium carbonate at 30-80 °C (e.g., 55 °C, etc.) to produce crude compound 8, which is recrystallized to produce compound 8.
[0061] As a non-limiting example, compound 9 can be prepared by aldol condensation of 1,4-cyclohexanedione with 4-6 equivalents (e.g., 5 equivalents, etc.) of an aqueous formaldehyde solution in the presence of 1-10 wt% (e.g., 5.5 wt%, etc.) calcium oxide at 30-80 °C (e.g., 55 °C, etc.) to produce tetrahydroxymethyl cyclohexanedione, followed by reaction of the tetrahydroxycyclohexanedione with 0.5-1.5 equivalents (e.g., 1 equivalent, etc.) of dichlorosulfoxide at 30-80 °C (e.g., 55 °C, etc.) to produce a sulfite ester, followed by oxidation of the sulfite ester with 0.1-1 wt% (e.g., 0.5 wt%, etc.) phosphotungstic acid catalysis and 0.5-2 equivalents (e.g., 1 equivalent, etc.) of hydrogen peroxide (e.g., 20% hydrogen peroxide by mass) at 30-80 °C (e.g., 55 °C, etc.) to produce crude compound 9, which is recrystallized to produce compound 9. with 2-10 equivalents (e.g., 6 equivalents, etc.) of dimethyl carbonate in the presence of 0.1-10 wt% (e.g., 5.5 wt%, etc.) of potassium carbonate Compound 9 was obtained by oxidation of 2-3 equivalents (e.g., 2.5 equivalents, etc.) of hydrogen peroxide (e.g., hydrogen peroxide with 20% mass content of hydrogen peroxide) in the presence of 0.1-1 wt% (e.g., 0.5 wt%, etc.) of phosphotungstic acid, and Compound 9 was obtained after recrystallization.
[0062] As a non-limiting enumeration, Compound 10 can be prepared by aldol condensation of 1,3-cyclopentanedione with 4-6 equivalents (e.g., 5 equivalents, etc.) of formaldehyde aqueous solution in the presence of 1-10 wt% (e.g., 5.5 wt%, etc.) of calcium oxide at 30-80°C (e.g., 55°C, etc.) to prepare tetrahydroxymethyl cyclopentanedione, and then reacting tetrahydroxymethyl cyclopentanedione with 0.5-1.5 equivalents (e.g., 1 equivalent, etc.) of dichlorosulfoxide at 30-80°C (e.g., 55°C, etc.) to prepare with 2-10 equivalents (e.g., 6 equivalents, etc.) of dimethyl carbonate in the presence of 0.1-10 wt% (e.g., 5.5 wt%, etc.) of potassium carbonate
[0063] Compound 10 was obtained by oxidation of 2-3 equivalents (e.g., 2.5 equivalents, etc.) of hydrogen peroxide (e.g., hydrogen peroxide with 20% mass content of hydrogen peroxide) in the presence of 0.1-1 wt% of phosphotungstic acid, and Compound 10 was obtained after recrystallization. Compound 10 was obtained by oxidation of 2-3 equivalents (e.g., 2.5 equivalents, etc.) of hydrogen peroxide (e.g., hydrogen peroxide with 20% mass content of hydrogen peroxide) in the presence of 0.1-1 wt% of phosphotungstic acid, and Compound 10 was obtained after recrystallization.
[0064] The above-mentioned equivalents and mass fractions are relative to the main reactants.
[0065] The electrolyte additive of the embodiments of the present application contains a compound having the structure shown in Formula 1, i.e., a cyclic structure containing sulfite groups, sulfite groups or carbonate groups at both ends connected together through a cyclic structure containing a ketone carbonyl group, wherein the ketone carbonyl group can coordinate with metal ions (e.g., lithium ions) in electrolyte salts, which is conducive to the movement of the additive to the electrode surface along with the current and the electrochemical reaction on the electrode surface; at the same time, when the cyclic structure undergoes electrochemical reaction, the ester group-containing ring can be opened to react with electrolyte salts (e.g., lithium salts) in the electrolyte to form organic electrolyte salts (e.g., organic lithium salts); at the same time, the cyclic ketone structure is opened to crosslink with organic matter in the battery or itself to form a double electrolyte salt (e.g., lithium salt) organic film with good stability, high structural strength and good ion permeability, thereby improving the high-temperature storage and high-temperature cycle performance of the battery.
[0066] <Electrolyte>
[0067] The electrolyte of the embodiments of the present application comprises a non-aqueous organic solvent, an electrolyte salt and the electrolyte additive of the embodiments of the present application.
[0068] In some embodiments, the compound of the structure of Formula 1 is present in the electrolyte in an amount of 0.05-10% by mass, including but not limited to 0.05%, 0.08%, 0.1%, 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.5%, 2.8%, 3%, 3.2%, 3.5%, 3.8%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 7.8%, 8%, 8.5%, 9%, 9.5%, or 10%, based on the total mass of the electrolyte.
[0069] In the embodiments of the present application, when the content of the compound of the structure of Formula 1 is within the above range, the stability of the film formed on the electrode surface can be effectively maintained, and the battery performance can be improved. If the content of the compound of the structure of Formula 1 is too low, the battery performance cannot be significantly improved. If the content of the compound of the structure of Formula 1 is too high, the decomposition products of the compound of the structure of Formula 1 can affect the performance of other substances in the electrolyte.
[0070] As a preferred example, the compound of the structure of Formula 1 is present in the electrolyte in an amount of 0.1-5% by mass, based on the total mass of the electrolyte.
[0071] In some embodiments, the electrolyte salt includes at least one of lithium salt, sodium salt, potassium salt, magnesium salt, zinc salt, and aluminum salt, etc.
[0072] As a preferred example, the electrolyte salt is lithium salt or sodium salt.
[0073] The alkali metal ions formed by the dissociation of the electrolyte salt in the electrolyte are deintercalated and intercalated between the positive electrode and the negative electrode to complete the charge and discharge cycle. The concentration of the electrolyte salt directly affects the transfer speed of the alkali metal ions, and the transfer speed of the alkali metal ions affects the potential change of the negative electrode. During the fast charging of the battery, it is necessary to increase the moving speed of the alkali metal ions as much as possible to prevent the formation of lithium dendrites caused by the rapid drop of the negative electrode potential, which may cause safety hazards to the battery, and also prevent the rapid decay of the cycle capacity of the battery. When the content of the electrolyte salt is too low, the intercalation and deintercalation efficiency of the alkali metal ions between the positive electrode and the negative electrode is reduced, which cannot meet the demand of fast charging of the battery. When the content of the electrolyte salt is too high, the viscosity of the non-aqueous electrolyte increases, which is also not conducive to the improvement of the intercalation and deintercalation efficiency of the alkali metal ions, and increases the internal resistance of the battery.
[0074] In some embodiments, the lithium salt includes, but is not limited to, at least one of LiPF6, LiBOB, LiDFOB, LiPO2F2, LiBF4, LiSbF6, LiAsF6, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiC(SO2CF3)3, LiN(SO2F)2, LiClO4, LiAlCl4, LiCF3SO3, Li2B 10 Cl 10 , lithium salts of lower aliphatic carboxylic acids, and the like.
[0075] In some embodiments, when the electrolyte salt is a lithium salt, the concentration of the lithium salt in the electrolyte is 0.1-8 mol / L, including but not limited to 0.1 mol / L, 0.5 mol / L, 1 mol / L, 1.5 mol / L, 2 mol / L, 2.5 mol / L, 3 mol / L, 3.5 mol / L, 4 mol / L, 4.5 mol / L, 5 mol / L, 5.5 mol / L, 6 mol / L, 6.5 mol / L, 7 mol / L, 7.5 mol / L, or 8 mol / L, and the like.
[0076] As a preferred example, when the electrolyte salt is a lithium salt, the concentration of the lithium salt in the electrolyte is 0.5-2.5 mol / L.
[0077] In some embodiments, the sodium salt includes, but is not limited to, at least one of sodium perchlorate (NaClO4), sodium hexafluorophosphate (NaPF6), sodium tetrafluoroborate (NaBF4), sodium bisfluorosulfonylimide (NaFSI), sodium trifluoromethylsulfonate (NaOTf), sodium bis-trifluoromethylsulfonylimide (NaTFSI), and the like.
[0078] In some embodiments, when the electrolyte salt is a sodium salt, and the concentration of the sodium salt in the electrolyte is 0.1-2 mol / L, including but not limited to 0.1 mol / L, 0.4 mol / L, 0.5 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L, 1 mol / L, 1.1 mol / L, 1.2 mol / L, 1.3 mol / L, 1.4 mol / L, 1.5 mol / L, or 2 mol / L, and the like.
[0079] As a preferred example, when the electrolyte salt is a sodium salt, and the concentration of the sodium salt in the electrolyte is 0.4-1.5 mol / L.
[0080] In some embodiments, the electrolyte further includes an auxiliary additive, and the auxiliary additive includes, but is not limited to, at least one of cyclic carbonate compounds, cyclic sulfate compounds, sulfonic acid lactone compounds, phosphate ester compounds, borate ester compounds, nitrile compounds, and the like.
[0081] In some embodiments, the cyclic carbonate compound includes, but is not limited to, at least one of vinylene carbonate, vinyl ethylene carbonate, methylene vinyl carbonate, fluoroethylene carbonate, trifluoromethyl ethylene carbonate, difluoroethylene carbonate, or a compound having a structure shown in Formula 2, and the like.
[0082]
[0083] In Formula 2, R 21 , R 22 , R 23 , R 24 , R 25 , R 26 are each independently selected from one of a hydrogen atom, a halogen atom, a C1-C5 group.
[0084] As a non-limiting list, the C1-C5 group includes, but is not limited to, a C1-C5 cyano group, a C1-C5 ester group, a C1-C5 alkyl group, a trifluoromethyl group, or a C1-C5 sulfonate group, and the like.
[0085] In embodiments of the present application, the term “cyano group” refers to -CN.
[0086] In embodiments of the present application, the term “ester group” is a functional group of an ester in a carboxylic acid derivative, with a structural formula of -COOR (R is generally an alkyl group or other non-H group).
[0087] In embodiments of the present application, the term “sulfonate group” refers to a group of Formula -O-SO2-R i , where R i is an alkyl group or the like.
[0088] As a preferred example, the compound having a structure shown in Formula 2 includes, but is not limited to, at least one of the following compounds 2-1 to 2-6:
[0089]
[0090] In some embodiments, the cyclic sulfate compound is selected from at least one of vinyl sulfate, 4-methyl vinyl sulfate, propylene sulfate, .
[0091] In some embodiments, the sulfonic acid lactone compound is selected from at least one of 1,3-propane sulfonic acid lactone, 1,4-butane sulfonic acid lactone, propylene-1,3-sulfonic acid lactone, .
[0092] In some embodiments, the phosphate compound includes a saturated phosphate compound and an unsaturated phosphate compound, wherein the saturated phosphate compound includes tris(trimethylsilyl)phosphate and the unsaturated phosphate compound includes a compound having the structure of Formula 3:
[0093] a compound having the structure of Formula 3:
[0094]
[0095] In Formula 3, R 31 , R 32 , and R 32 are each independently selected from a C1-C5 saturated hydrocarbon group, a C1-C5 unsaturated hydrocarbon group, a C1-C5 halogenated hydrocarbon group, or -Si(C m H 2m+1 )3, m is a natural number from 1 to 3, and R 31 , R 32 , and R 33 are each independently selected from a C1-C5 saturated hydrocarbon group, a C1-C5 unsaturated hydrocarbon group, a C1-C5 halogenated hydrocarbon group, or -Si(C m H 2m+1 )3.
[0096] In embodiments of the present application, the term "saturated hydrocarbon group" or "alkyl group" refers to a straight chain or branched alkyl radical containing from 1 to 5 carbon atoms. For example, methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, t-butyl, pentyl, isopentyl, and the like.
[0097] In embodiments of the present application, the term "unsaturated hydrocarbon group" refers to a hydrocarbon compound having a carbon-carbon double or triple bond in the molecule.
[0098] By way of non-limiting example, the C1-C5 unsaturated hydrocarbon group includes, but is not limited to, a vinyl group, an ethynyl group, a propenyl group, a 2-methylpropenyl group, a 1,4-butadienyl group, a propynyl group, and the like. The C1-C5 halogenated hydrocarbon group includes, but is not limited to, a trifluoromethyl group, a trifluoroethyl group, a monofluorinated propyl group, a monofluorinated butyl group, a difluorinated pentyl group, and the like.
[0099] By way of non-limiting example, m has a value of 1, 2, or 3, i.e., Si(C m H 2m+1 )3 is Si(CH3)3, Si(C2H5)3, or Si(C3H7)3.
[0100] As a preferred example, the compound having a structure represented by Formula 3 includes, but is not limited to, at least one of tripropargyl phosphate, dipropargyl methyl phosphate, dipropargyl ethyl phosphate, dipropargyl propyl phosphate, dipropargyl trifluoromethyl phosphate, dipropargyl-2,2,2-trifluoroethyl phosphate, dipropargyl-3,3,3-trifluoropropyl phosphate, dipropargyl hexafluoroisopropyl phosphate, triallyl phosphate, diallyl methyl phosphate, diallyl ethyl phosphate, diallyl propyl phosphate, diallyl trifluoromethyl phosphate, diallyl-2,2,2-trifluoroethyl phosphate, diallyl-3,3,3-trifluoropropyl phosphate, diallyl hexafluoroisopropyl phosphate, and the like.
[0101] In some embodiments, the borate compound includes, but is not limited to, at least one of tris(trimethylsilyl) borate, tris(triethylsilyl) borate, and the like.
[0102] In some embodiments, the nitrile compound includes, but is not limited to, at least one of butanedinitrile, pentanedinitrile, ethylene glycol bis(propionitrile) ether, hexanetristitnile, hexanedinitrile, heptanedinitrile, octanedinitrile, nonanedinitrile, decanedinitrile, and the like.
[0103] In the embodiments of the present application, the content of the auxiliary additive in the electrolyte, based on the total mass of the electrolyte being 100%, varies depending on the selection of the type of the auxiliary additive. Specifically, in some embodiments, when the auxiliary additive is selected from at least one of the other substances in the above-mentioned cyclic carbonate compound, cyclic sulfate compound, sulfolane compound, phosphate compound, borate compound, and nitrile compound, other than the fluoroethylene carbonate, the content of any of the optional substances in the non-aqueous electrolyte is 10% or less, including but not limited to 0.05%, 0.08%, 0.1%, 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.5%, 2.8%, 3%, 3.2%, 3.5%, 3.8%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 7.8%, 8%, 8.5%, 9%, 9.5%, 10%, and the like; preferably, the content of any of the optional substances in the non-aqueous electrolyte is 0.1-5%, more preferably 0.1%-3%. In other embodiments, when the auxiliary additive is selected to be the fluoroethylene carbonate, the content of the fluoroethylene carbonate is 0.05%-30%, based on the total mass of the electrolyte being 100%, including but not limited to 0.05%, 1%, 2.5%, 5%, 7.5%, 10%, 12.5%, 15%, 17.5%, 20%, 22.5%, 25%, 27.5%, or 30%, and the like.
[0104] The electrolyte of the embodiment of the present application, compared with single addition or combination of other existing additives, the compound shown in the above structural formula 1 and the above auxiliary additive added together, in improving the battery performance, shows obvious synergistic effect, which shows that the compound shown in the structural formula 1 and the auxiliary additive can form a film together on the electrode surface to make up for the film forming defect of single addition, and a more stable passivation film is obtained.
[0105] In some embodiments, the non-aqueous organic solvent includes, but is not limited to, at least one of an ether solvent, a nitrile solvent, a carbonate solvent, a carboxylate solvent, and a sulfone solvent, etc.
[0106] In some embodiments, the ether solvent includes a cyclic ether or a chain ether.
[0107] As a non-limiting enumeration, the cyclic ether can be, but is not limited to, at least one of 1,3-dioxolane (DOL), 1,4-dioxane (DX), crown ether, tetrahydrofuran (THF), 2-methyltetrahydrofuran (2-CH3-THF), 2-trifluoromethyltetrahydrofuran (2-CF3-THF), etc.
[0108] As a non-limiting enumeration, the chain ether can be, but is not limited to, at least one of dimethoxymethane (DMM), 1,2-dimethoxyethane (DME), diglyme (TEGDME), etc.
[0109] As a non-limiting enumeration, the nitrile solvent can be, but is not limited to, at least one of acetonitrile, glutaronitrile, malononitrile, etc.
[0110] In some embodiments, the carbonate solvent includes, but is not limited to, a cyclic carbonate or a chain carbonate.
[0111] As a non-limiting enumeration, the cyclic carbonate can be, but is not limited to, at least one of ethylene carbonate (EC), propylene carbonate (PC), gamma-butyrolactone (GBL), butylene carbonate (BC), etc.
[0112] As a non-limiting enumeration, the chain carbonate can be, but is not limited to, at least one of dimethyl carbonate (DMC), methyl ethyl carbonate (EMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), etc.
[0113] As a non-limiting enumeration, the carboxylate solvent can be, but is not limited to, at least one of methyl acetate (MA), ethyl acetate (EA), propyl acetate (EP), butyl acetate, propyl propionate (PP), butyl propionate, etc.
[0114] As a non-limiting enumeration, sulfone solvents include, but are not limited to, at least one of dimethyl sulfoxide, sulfolane, diethyl sulfone, methyl ethyl sulfone, or dimethyl sulfone, and the like.
[0115] <Secondary battery>
[0116] The secondary battery of the embodiments of the present application comprises a positive electrode, a negative electrode, and an electrolyte, wherein the electrolyte is the electrolyte of the embodiments of the present application.
[0117] In some embodiments, the secondary battery is selected from a lithium metal battery, a lithium ion battery, a lithium-sulfur battery, a sodium ion battery, a magnesium ion battery, a potassium ion battery, a zinc ion battery, or an aluminum-lithium sub-battery.
[0118] In some embodiments, the positive electrode comprises a positive electrode material layer, and the positive electrode material layer comprises a positive electrode active material, which is not particularly limited in type and content, and can be selected according to actual needs, as long as it is a positive electrode active material or a conversion-type positive electrode material capable of reversibly intercalating / deintercalating metal ions (lithium ions, sodium ions, potassium ions, magnesium ions, zinc ions, aluminum ions, etc.).
[0119] As a preferred example, the secondary battery is a lithium ion battery, and the positive electrode active material of the secondary battery includes, but is not limited to, at least one of lithium-containing sulfides, lithium-containing selenides, lithium-containing halides, LiFePO4, LiFe 1-x’ M’ x’ PO4, LiMn 2-y’ M y’ O4, and LiNi x Co y Mn z M 1-x-y-z O2, and the like, wherein M’ includes, but is not limited to, at least one of Mn, Mg, Co, Ni, Cu, Zn, Al, Sn, B, Ga, Cr, Sr, V, or Ti, and the like, M includes, but is not limited to, at least one of Fe, Co, Ni, Mn, Mg, Cu, Zn, Al, Sn, B, Ga, Cr, Sr, V, or Ti, and the like, and 0≤x’<1, 0≤y’≤1, 0≤y≤1, 0≤x≤1, 0≤z≤1, x+y+z≤1.
[0120] As a non-limiting enumeration, the values of x’, y’, y, x, z, and x+y+z include, but are not limited to, 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, or 1, and the like.
[0121] As a more preferred example, when the secondary battery is a lithium ion battery, the positive electrode active material of the secondary battery can be selected from LiCoO2, LiFePO4, LiFe 0.8 Mn 0.2PO4, LiMn2O4, LiNi 0.5 Co 0.2 Mn 0.3 O2, LiNi 0.6 Co 0.2 Mn 0.2 O2, LiNi 0.8 Co 0.1 Mn 0.1 O2, LiNi 0.5 Co 0.2 Mn 0.2 Al 0.1 O2, LiNi 0.5 Co 0.2 Al 0.3 At least one of O2.
[0122] In other embodiments, the secondary battery is a sodium-ion battery, and the positive electrode active material includes, but is not limited to, at least one of sodium-containing transition metal oxides, sodium-containing Prussian materials, sodium-containing phosphates, sodium-containing sulfates, and sodium-containing titanates.
[0123] In some embodiments, the sodium-containing transition metal oxide may be Na. a T b O c T includes, but is not limited to, at least one of Cr, Fe, Co, Ni, Cu, Mn, Sn, Mo, Sb, V, etc., where 1≤a≤10, 1≤b≤5, and 1≤c≤20.
[0124] As a non-restrictive enumeration, the values of a include, but are not limited to, 1, 3, 5, 8, or 10; the values of b include, but are not limited to, 1, 2, 3, 4, or 5; and the values of c include, but are not limited to, 1, 3, 5, 7, 10, 13, 15, or 19.
[0125] More preferably, the sodium-containing transition metal oxide is NaNi. m Fe n Mn p O2 (m+n+p=1, 0≤m≤1, 0≤n≤1, 0≤p≤1) or NaNi m Co n Mn p O2(m+n+p=1, 0≤m≤1, 0≤n≤1, 0≤p≤1).
[0126] As a non-restrictive enumeration, the values of m, n, and p include, but are not limited to, 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, or 1.
[0127] In some embodiments, the molecular formula of the sodium-containing Prussian-like material is Na.d Q[Q'(CN)6] e • fH20, wherein Q is a transition metal, Q' is a transition metal, 0 < d < 2, 0.8 < e < 1, 0 < f < 20.
[0128] As a non-limiting enumeration, Q, Q' each includes, but is not limited to, at least one of Cr, Fe, Co, Ni, Cu, Mn, Mo, V, Ti, Zr, and the like.
[0129] As a non-limiting enumeration, the values of d each include, but are not limited to, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.3, 1.5, 1.8, or 2, and the like.
[0130] As a non-limiting enumeration, the values of e each include, but are not limited to, 0.8, 0.85, 0.9, or 0.95, and the like.
[0131] As a non-limiting enumeration, the values of f each include, but are not limited to, 0.1, 0.5, 1, 5, 10, 15, or 20, and the like.
[0132] More preferably, the sodium-containing Prussian-type material is Na h Mn[Fe(CN)6] i • jH20 (0 < h < 2, 0 < i < 1, 0 < j < 10) or Na h Fe[Fe(CN)6] i • jH20 (0 < h < 2, 0 < i < 1, 0 < j < 10).
[0133] As a non-limiting enumeration, the values of h each include, but are not limited to, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.3, 1.5, 1.8, or 2, and the like.
[0134] As a non-limiting enumeration, the values of i each include, but are not limited to, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, or 1, and the like.
[0135] As a non-limiting enumeration, the values of j each include, but are not limited to, 0.1, 0.5, 1, 3, 5, 8, or 10, and the like.
[0136] In some embodiments, the sodium-containing phosphate has a chemical formula of Na3(GO 1-k PO4)2F 1+2k , 0 < k < 1, G is selected from at least one of Al, V, Ge, Fe, Ga, and more preferably, the sodium-containing phosphate is Na3(VPO4)2F3 or Na3(VOPO4)2F.
[0137] As a non-limiting enumeration, the values of k include, but are not limited to, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, or 1, etc.
[0138] In some embodiments, the sodium-containing phosphate salt has a chemical formula of Na2JPO4F, J is selected from at least one of Fe, Mn, and more preferably, the sodium-containing phosphate salt is Na2FePO4F or Na2MnPO4F.
[0139] In some embodiments, the sodium-containing titanate material includes, but is not limited to, at least one of Na2Ti3O7, Na2Ti6O 13 , Na4Ti5O 12 , Li4Ti5O 12 , NaTi2(PO4)3, etc.
[0140] In some embodiments, the sodium-containing sulfate salt has a chemical formula of Na2Z(SO4)2·2H2O, Z is selected from at least one of Cr, Fe, Co, Ni, Cu, Mn, Sn, Mo, Sb, V.
[0141] In some embodiments, the positive electrode further includes a positive electrode current collector, and the positive electrode material layer is disposed on a surface of the positive electrode current collector.
[0142] In some embodiments, the positive electrode current collector is selected from a metal material capable of conducting electrons, and preferably, the positive electrode current collector includes at least one of Al, Ni, tin, copper, and stainless steel, and in a more preferred embodiment, the positive electrode current collector is selected from an aluminum foil.
[0143] In some embodiments, the positive electrode active material layer further includes a positive electrode binder and a positive electrode conductive agent, and the positive electrode active material, the positive electrode binder, and the positive electrode conductive agent are blended to obtain the positive electrode material layer.
[0144] In some embodiments, the positive electrode binder includes, but is not limited to, at least one of polyvinylidene fluoride, a copolymer of polyvinylidene fluoride, polytetrafluoroethylene, a copolymer of polyvinylidene fluoride-hexafluoropropylene, a copolymer of tetrafluoroethylene-hexafluoropropylene, a copolymer of tetrafluoroethylene-perfluoroalkyl vinyl ether, a copolymer of ethylene-tetrafluoroethylene, a copolymer of polyvinylidene fluoride-tetrafluoroethylene, a copolymer of polyvinylidene fluoride-trifluoroethylene, a copolymer of polyvinylidene fluoride-trichloroethylene, a copolymer of polyvinylidene fluoride-fluoroethylene, a copolymer of polyvinylidene fluoride-hexafluoropropylene-tetrafluoroethylene, a thermoplastic polyimide, a thermoplastic resin of polyethylene and polypropylene, an acrylic resin, and a styrene butadiene rubber.
[0145] In some embodiments, the positive electrode conductive agent includes, but is not limited to, at least one of conductive carbon black, conductive carbon spheres, conductive graphite, conductive carbon fibers, carbon nanotubes, graphene, or reduced graphene oxide, etc.
[0146] In some embodiments, the above-mentioned negative electrode comprises a negative electrode material layer, and the negative electrode material layer comprises a negative electrode active material. The type and content of the negative electrode active material are not particularly limited and can be selected according to actual needs.
[0147] In preferred embodiments, the secondary battery is a lithium ion battery, and the negative electrode active material comprises at least one of, but is not limited to, a carbon-based negative electrode, a silicon-based negative electrode, a tin-based negative electrode, a lithium negative electrode, etc. The carbon-based negative electrode can comprise graphite, hard carbon, soft carbon, graphene, mesocarbon microbeads, etc.; the silicon-based negative electrode can comprise silicon material, silicon oxide, silicon-carbon composite material, and silicon alloy material, etc.; the tin-based negative electrode can comprise tin, tin-carbon, tin oxide, tin metal compound; and the lithium negative electrode can comprise metallic lithium or lithium alloy. The lithium alloy can be at least one of lithium-silicon alloy, lithium-sodium alloy, lithium-potassium alloy, lithium-aluminum alloy, lithium-tin alloy, and lithium-indium alloy.
[0148] In preferred embodiments, the secondary battery is a sodium ion battery, and the negative electrode active material comprises at least one of, but is not limited to, metallic sodium, graphite, soft carbon, hard carbon, carbon fiber, mesocarbon microbead, silicon-based material, tin-based material, lithium titanate, or other alloy material capable of forming an alloy with sodium, etc. The alloy material can further comprise at least one of Si, Ge, Sn, Pb, and Sb and C; the graphite can be at least one of artificial graphite, natural graphite, and modified graphite; the silicon-based material can be at least one of elemental silicon, silicon oxide compound, silicon-carbon composite, and silicon alloy; and the tin-based material can be at least one of elemental tin, tin oxide compound, and tin alloy.
[0149] In some embodiments, the above-mentioned negative electrode further comprises a negative electrode current collector, and the negative electrode material layer is arranged on the surface of the negative electrode current collector. The material of the negative electrode current collector can be the same as that of the above-mentioned positive electrode current collector, which will not be described herein again.
[0150] In some embodiments, the above-mentioned negative electrode material layer further comprises a negative electrode binder and a negative electrode conductive agent, and the negative electrode active material, the negative electrode binder, and the negative electrode conductive agent are blended to obtain the above-mentioned negative electrode material layer. The negative electrode binder and the negative electrode conductive agent can be the same as the above-mentioned positive electrode binder and the positive electrode conductive agent, respectively, which will not be described herein again.
[0151] In some embodiments, the secondary battery further comprises a separator, and the separator is located between the positive electrode and the negative electrode.
[0152] In some embodiments, the separator can be a conventional separator, which can be a ceramic separator, a polymer separator, a non-woven fabric, an inorganic-organic composite separator, etc., including but not limited to single-layer PP (polypropylene) separator, single-layer PE (polyethylene) separator, double-layer PP / PE separator, double-layer PP / PP separator, and three-layer PP / PE / PP separator.
[0153] The secondary battery of the present application embodiment adopts the electrolyte of the present application embodiment, and the compound shown in Structural Formula 1 can form a passivation film with excellent performance on the positive electrode and the negative electrode, thereby effectively improving the high-temperature storage performance and the high-temperature cycle performance of the battery and improving the power characteristics of the battery. In addition, the secondary battery of the present application embodiment adopts the electrolyte of the present application embodiment, and it is reasonably speculated that the coordination of the ketone carbonyl group in the compound shown in Structural Formula 1 with the metal (e.g., lithium) in the electrolyte salt can move to the electrode surface with the current to undergo an electrochemical reaction, the ring sulfuric acid ester, the ring sulfurous acid ester, and the ring carbonate are opened to form an organic sulfuric acid / sulfurous acid / carbonate electrolyte salt (e.g., organic lithium sulfate), and at the same time, the ketone carbonyl group is opened and cross-linked to form a double electrolyte salt (e.g., lithium salt) organic film with good stability, high structural strength, and good ion permeability, thereby improving the high-temperature storage and high-temperature cycle performance of the battery.
[0154] Certain features of the present technology are further illustrated in the following non-limiting examples.
[0155] I. Performance Test
[0156] 1. Test of high-temperature cycle performance
[0157] The test method is as follows: after formation, the battery is placed at 45°C for 2h, and then charged at a rate of 0.5C to 4.0V, and then charged at a constant voltage until the current is 0.03C, and then discharged at a constant current of 1C to 1.5V, and then cycled for 1000 cycles.
[0158] The initial discharge capacity D1 of the battery, the initial battery volume V1, the retention capacity D2 after 1000 cycles, the recovery capacity D3, and the battery volume V2 after cycling are measured, and the battery coulombic efficiency E is calculated.
[0159] The calculation formula is as follows:
[0160] The capacity retention rate (%) of the battery after 1000 cycles = capacity D2 / initial capacity D1 x 100%;
[0161] The capacity recovery rate (%) of the battery after 1000 cycles = capacity D3 / initial capacity D1 x 100%
[0162] The volume expansion rate (%) = (battery volume V2 after cycling-initial battery volume V1) / initial battery volume V1 x 100%.
[0163] 2. Test of high-temperature storage performance
[0164] The test method is as follows: after formation, the battery is charged at room temperature with a current of 0.5C to 4.0V, then charged at constant voltage until the current drops to 0.03C, then discharged at a current of 1C to 1.5V, the initial discharge capacity D1, the initial battery volume V1 and the initial impedance F1 of the battery are measured, then charged to full charge, stored at 60°C for 30 days, then discharged at 1C to 3V, the retention capacity D2, the recovery capacity D3, the impedance F2 after storage and the battery volume V2 after storage are measured.
[0165] The calculation formula is as follows:
[0166] Battery capacity retention rate (%) = retention capacity D2 / initial capacity D1 x 100%;
[0167] Battery capacity recovery rate (%) = recovery capacity D3 / initial capacity D1 x 100%;
[0168] Volume expansion rate (%) = (battery volume after storage V2-initial battery volume V1) / initial battery volume V1 x 100%;
[0169] Internal resistance growth rate (%) = impedance F2 after storage / initial impedance F1 x 100%.
[0170] II. Examples and Comparative Examples
[0171] The compounds involved in each example and comparative example are shown in Table 1:
[0172] Table 1 Compounds involved in each example and comparative example
[0173]
[0174]
[0175] 1. Lithium ion battery (Examples 1-18 and Comparative Examples 1-9)
[0176] Example 1
[0177] Preparation method of electrolyte
[0178] The preparation method of the electrolyte of this example is as follows: ethylene carbonate (EC), diethyl carbonate (DEC) and methyl ethyl carbonate (EMC) are mixed in a mass ratio of EC:DEC:EMC=0.9:1:1, then lithium hexafluorophosphate (LiPF6) is added to a molar concentration of 1.1 mol / L, 0.05% of an additive is added based on the total weight of the electrolyte, and the additive is compound 1.
[0179] Preparation method of lithium ion battery
[0180] The preparation method of the lithium ion battery of the present embodiment comprises the following steps:
[0181] 1) Preparation of the positive electrode: mix the positive electrode active material lithium nickel cobalt manganese oxide LiNi 0.5 Co 0.2 Mn 0.3 O2, conductive carbon black Super-P and binder polyvinylidene fluoride (PVDF) in a mass ratio of 93:4:3, and then disperse them in N-methyl-2-pyrrolidone (NMP) to obtain a positive electrode slurry with a viscosity of about 6000 mPa.s. The slurry is uniformly coated on the opposite two sides of an aluminum foil with a thickness of 18 μm, and then subjected to drying, calendering and vacuum drying, and an aluminum lead is welded on the positive electrode sheet by an ultrasonic welding machine to obtain a positive electrode sheet with a thickness of 120 μm.
[0182] 2) Preparation of the negative electrode sheet:
[0183] Mix the negative electrode active material artificial graphite, conductive carbon black Super-P, binder styrene-butadiene rubber (SBR) and carboxymethyl cellulose (CMC) in a mass ratio of 94:1:2.5:2.5, and then disperse them in deionized water to obtain a negative electrode slurry with a viscosity of about 4000 mPa.s. The slurry is coated on the opposite two sides of a copper foil with a thickness of 8 μm, and then subjected to drying, calendering and vacuum drying, and a nickel lead is welded on the negative electrode sheet by an ultrasonic welding machine to obtain a negative electrode sheet with a thickness of 120 μm.
[0184] 3) Preparation of the battery cell:
[0185] Place a three-layer PP / PE / PP separator with a thickness of 20 μm between the positive electrode and the negative electrode, and then roll the sandwich structure of the positive electrode, the negative electrode and the separator, and then flatten the rolled body and place it in an aluminum foil packaging bag, and vacuum bake at 75 °C for 48 h to obtain a battery cell to be injected with electrolyte.
[0186] 4) Injection of electrolyte and formation of the battery cell:
[0187] Inject the electrolyte prepared in the present embodiment into the battery cell in a glove box with the dew point controlled below -40 °C, and vacuum seal, and stand still for 24 h.
[0188] Then perform the conventional formation of the first charge in the following steps: 0.05 C constant current charging for 180 min, 0.2 C constant current charging to 3.95 V, twice vacuum sealing, and then further constant current charging to 4.2 V at a current of 0.2 C, and after standing still at room temperature for 24 h, constant current discharging to 3.0 V at a current of 0.2 C to obtain a LiNi 0.5 Co 0.2 Mn 0.3 O2 / artificial graphite lithium ion battery.
[0189] Examples 1-18 and Comparative Examples 1-9 are basically the same as Example 1, except that the selection of the substances of the additives and the amount of the additives are different. It should be noted that the additives herein include the compound shown in Structural Formula 1 (electrolyte additive) and / or auxiliary additive.
[0190] Examples 1-9 and Comparative Examples 1-5 investigate the influence of the compound shown in Structural Formula 1 in different amounts, the specific amount of the same electrolyte additive of the present application, the combination of the auxiliary additive, the non-use of any additive, and the use of only the auxiliary additive on the high-temperature cycle performance of the lithium ion battery, as shown in Tables 2 and 3.
[0191] Table 2: Selection of some substances and parameters and high-temperature cycle performance of Examples 1-9 and Comparative Examples 1-5
[0192]
[0193] According to Table 2:
[0194] The test results of Comparative Examples 1-8 show that as the amount of the compound 1 shown in Structural Formula 1 increases, the volume expansion rate of the lithium ion battery can first decrease and then increase, the capacity retention rate and the capacity recovery rate can first increase and then decrease, indicating that too much or too little amount of the compound 1 shown in Structural Formula 1 can improve the high-temperature cycle performance of the lithium ion battery, and especially when the amount of the compound 1 shown in Structural Formula 1 is 0.5-5wt%, the lithium ion battery has the optimal high-temperature cycle performance.
[0195] The test results of Comparative Examples 1-8 and Comparative Example 1-4 show that compared with the traditional vinyl carbonate (VC), vinyl sulfate (DTD) and 1,3-propane sulfonate (PS), the use of the compound 1 shown in Structural Formula 1 provided by the present application as an additive can more obviously improve the cycle performance of the lithium ion battery at high temperature, indicating that the passivation film formed by the compound 1 shown in Structural Formula 1 is more stable and has more excellent lithium ion permeability.
[0196] The test results of Comparative Example 9 and Comparative Example 5 show that when the compound 1 shown in Structural Formula 1 provided by the present application and vinyl carbonate (VC) are used as additives at the same time, the cycle performance of the lithium ion battery at high temperature can be further improved compared with the use of DTD and vinyl carbonate (VC) as additives.
[0197] Examples 4, 10-18 and Comparative Examples 1-4 investigate the influence of the different compounds shown in Structural Formula 1 at the same amount, the non-use of any additive, and the use of only the auxiliary additive on the high-temperature cycle performance of the lithium ion battery, as shown in Table 3.
[0198] Table 3: Selection of some substances and parameters and high-temperature cycle performance of Examples 4, 10-18 and Comparative Examples 1-4
[0199]
[0200]
[0201] The test results of Comparative Examples 4, 10-18 and Comparative Examples 1-4 show that, compared with lithium ion batteries without additives or with existing additives, the lithium ion batteries obtained by using the compound represented by structural formula 1 as an additive have better high-temperature cycle performance.
[0202] Comparative Example 6 (the ring containing a carbonyl group in the middle of structural formula 1 is replaced by a non-ring structure containing a carbonyl group)
[0203] This comparative example is basically the same as Example 4, except that:
[0204] Compound 11 is used to replace compound 1 in the electrolyte.
[0205] Comparative Example 7 (the ring containing a carbonyl group in the middle of structural formula 1 is replaced by a ring structure not containing a carbonyl group)
[0206] This comparative example is basically the same as Example 4, except that:
[0207] Compound 12 is used to replace compound 1 in the electrolyte.
[0208] Comparative Example 8 (the ring containing a carbonyl group in the middle of structural formula 1 is replaced by a non-ring structure containing a carbonyl group)
[0209] This comparative example is basically the same as Example 9, except that:
[0210] Compound 11 is used to replace compound 1 in the electrolyte.
[0211] Comparative Example 9 (the ring containing a carbonyl group in the middle of structural formula 1 is replaced by a ring structure not containing a carbonyl group)
[0212] This comparative example is basically the same as Example 9, except that:
[0213] Compound 12 is used to replace compound 1 in the electrolyte.
[0214] The high-temperature cycle performance test results of the lithium ion batteries corresponding to Examples 4, 9 and Comparative Examples 6-9 are shown in Table 4.
[0215] Table 4: Selection of some substances and parameters, high-temperature cycle performance of Examples 4, 9 and Comparative Examples 6-9
[0216]
[0217]
[0218] As can be seen from Table 4, from Examples 4, 9 and Comparative Examples 6, 8, only having a carbonyl structure, the high-temperature cycle performance is also better than that of the currently used additive, but not as good as that of Compound 1, it is speculated that without a cyclic structure, the cross-linked structure formed after oxidation of the carbonyl group is not as stable as that of Compound 1; from Examples 4, 9 and Comparative Examples 7, 9, only having a cyclic structure, the high-temperature cycle performance is comparable to that of the currently used additive, but not as good as that of Compound 1, it is speculated that without a carbonyl structure, the cross-linked structure cannot be formed, resulting in a film strength that is not as good as that of Compound 1.
[0219] 2. Sodium-ion battery (Examples 19-36 and Comparative Examples 10-15)
[0220] Example 19
[0221] Preparation method of electrolyte
[0222] The preparation method of the electrolyte of the present example is to mix ethylene carbonate (EC), diethyl carbonate (DEC) and methyl ethyl carbonate (EMC) in a mass ratio of EC:DEC:EMC = 1:1:1, then add sodium hexafluorophosphate (NaPF6) to a molar concentration of 1 mol / L, 0.05% additive is added based on the total weight of the electrolyte, and the additive is Compound 1.
[0223] Preparation method of sodium-ion battery
[0224] The preparation method of the sodium-ion battery of the present example comprises the following steps:
[0225] 1) Preparation of positive electrode sheet:
[0226] Mix the positive electrode active material Na3V2(PO4)3, conductive carbon black Super-P and the binder polyvinylidene fluoride (PVDF) in a mass ratio of 94:3:3, then disperse them in N-methyl-2-pyrrolidone (NMP) to obtain a positive electrode slurry with a viscosity of about 8000 mPa.s. The slurry is uniformly coated on both sides of a 15 μm aluminum foil, dried, calendered and vacuum dried, and then an aluminum lead wire is welded on using an ultrasonic welding machine to obtain a positive electrode sheet with a thickness of 150 μm.
[0227] 2) Preparation of negative electrode sheet:
[0228] Mix the negative electrode active material spherical hard carbon, conductive carbon black Super-P, the binder styrene-butadiene rubber (SBR) and carboxymethyl cellulose (CMC) in a mass ratio of 97:1:1:1, then disperse them in deionized water to obtain a negative electrode slurry with a viscosity of about 5000 mPa.s. The slurry is coated on both sides of a 15 μm aluminum foil, dried, calendered and vacuum dried, and then a nickel lead wire is welded on using an ultrasonic welding machine to obtain a negative electrode sheet with a thickness of 150 μm.
[0229] 3) The positive electrode sheet, the separator (20 pm three-layer PP / PE / PP separator), and the negative electrode sheet were stacked in order, packaged with an aluminum plastic film, roasted, injected with liquid, left to stand, formed with a jig, sealed, and tested for capacity to complete the preparation of the sodium-ion battery.
[0230] Examples 20-36 and Comparative Examples 10-15 are basically the same as Example 19, except that the substance selection and amount of some additives are different. It should be noted that the additives here include the compound shown in structural formula 1 (electrolyte additive) and / or auxiliary additive.
[0231] wherein:
[0232] Examples 19-27 and Comparative Examples 10 and 11 investigate the effects of different amounts of the compound shown in structural formula 1, the use of the same electrolyte additive in a specific amount in combination with an auxiliary additive, the use of no additives, and the use of only an auxiliary additive on the high-temperature storage performance of sodium-ion batteries, as shown in Table 5.
[0233] Table 5: Substance and parameter selection and high-temperature storage performance of Examples 19-27 and Comparative Examples 10 and 11
[0234]
[0235] According to Table 5:
[0236] The test results of Comparative Examples 19-27 show that as the amount of compound 1 shown in structural formula 1 increases, the volume expansion rate and internal resistance increase rate of the lithium-ion battery first decrease and then increase, and the capacity retention rate first increases and then decreases, indicating that too much or too little additive amount can improve the high-temperature storage performance of the sodium-ion battery and reduce its internal resistance growth. In particular, when the amount of compound 1 shown in structural formula 1 is 0.5-5%, the sodium-ion battery has the optimal impedance reduction and high-temperature storage performance.
[0237] Comparative Examples 22 and Comparative Examples 10-11 show that compared with the case of not adding any additives and the case of adding existing additives, the high-temperature storage performance of the sodium-ion battery is greatly improved when compound 1 shown in structural formula 1 is added to the electrolyte.
[0238] Examples 22, 28-36 and Comparative Examples 10 and 11 investigate the effects of different amounts of the compound shown in structural formula 1, the use of no additives, and the use of only an auxiliary additive on the high-temperature cycle performance of sodium-ion batteries, as shown in Table 6.
[0239] Table 6: Substance and parameter selection and high-temperature storage performance of Examples 22, 28-36 and Comparative Examples 10-11
[0240]
[0241] According to Table 6:
[0242] The test results of Examples 22, 28-36 and Comparative Examples 10, 11 show that, compared with sodium ion batteries without additives or with existing additives, the sodium ion batteries obtained by using the compound represented by structural formula 1 as an additive have better high-temperature storage performance.
[0243] Comparative Example 12 (the ring containing a carbonyl group in the middle of structural formula 1 is replaced by a non-ring structure containing a carbonyl group)
[0244] This comparative example is basically the same as Example 19, except that:
[0245] Compound 11 is used to replace compound 1 in the electrolyte.
[0246] Comparative Example 13 (the ring containing a carbonyl group in the middle of structural formula 2 is replaced by a ring structure not containing a carbonyl group)
[0247] This comparative example is basically the same as Example 22, except that:
[0248] Compound 12 is used to replace compound 1 in the electrolyte.
[0249] Comparative Example 14 (the ring containing a carbonyl group in the middle of structural formula 1 is replaced by a non-ring structure containing a carbonyl group)
[0250] This comparative example is basically the same as Example 19, except that:
[0251] Compound 11 is used to replace compound 1 in the electrolyte.
[0252] Comparative Example 15 (the ring containing a carbonyl group in the middle of structural formula 1 is replaced by a ring structure not containing a carbonyl group)
[0253] This comparative example is basically the same as Example 22, except that:
[0254] Compound 12 is used to replace compound 1 in the electrolyte.
[0255] The high-temperature cycle performance test results of the sodium ion batteries corresponding to Examples 19, 22 and Comparative Examples 10-15 are shown in Table 7.
[0256] Table 7: Selection of some substances and parameters, high-temperature storage performance of Examples 19, 22 and Comparative Examples 10-15
[0257]
[0258] As can be seen from Table 7, it can be seen from Examples 22 and Comparative Examples 10, 11, 13, 15 that only the carbonyl structure has a high-temperature storage performance superior to that of the currently used additive but not as good as that of Compound 1, and it is presumed that the crosslinked structure formed by oxidation of the carbonyl group without a cyclic structure is not as stable as that of Compound 1, and the film strength is not as good as that of Compound 1 because the crosslinked structure cannot be formed without the carbonyl structure.
[0259] As can be seen from Examples 19 and Comparative Examples 10, 12, 14, it can be seen that only the carbonyl structure has a high-temperature storage performance superior to that of the additive-free sample but not as good as that of Compound 1, and it is presumed that the crosslinked structure formed by oxidation of the carbonyl group without a cyclic structure is not as stable as that of Compound 1, and the film strength is not as good as that of Compound 1 because the crosslinked structure cannot be formed without the carbonyl structure.
[0260] In the present application, the terms "one embodiment", "some embodiments", "example", "specific example" or "some examples" mean that the specific feature, structure, material or characteristic being described is included in at least one embodiment or example of the present application. Descriptive terms such as "exemplary" or "specific example" do not necessarily refer to the same embodiment or example in the present specification. Also, the specific features, structures, materials or characteristics described can be combined in any suitable manner in any one or more embodiments or examples. In addition, different embodiments or examples described in the present specification and the features of different embodiments or examples can be combined and combined by those skilled in the art without contradiction.
[0261] Although the embodiments of the present application have been shown and described above, it is understood that the above-described embodiments are exemplary and are not to be construed as limiting the present application, and those skilled in the art can make changes, modifications, replacements and variations to the above-described embodiments within the scope of the present application.
Claims
1. An electrolyte additive characterized in that, The compound includes a compound having a structure shown in Formula 1: wherein X, Y are each independently selected from R1, R2are each independently selected from a single bond, substituted or unsubstituted -CH2-, substituted or unsubstituted -CH2-CH2-.
2. The electrolyte additive according to claim 1, characterized in that, The substituent in the substituted or unsubstituted -CH2- and the substituted or unsubstituted -CH2-CH2- is halogen.
3. The electrolyte additive according to claim 1, characterized in that, The compound having the structure shown in Formula 1 includes at least one of Compound 1 to Compound 10:
4. An electrolyte, characterized by The non-aqueous organic solvent includes at least one of an ether solvent, a nitrile solvent, a carbonate solvent, a carboxylate solvent, and a sulfone solvent.
5. The electrolyte according to claim 4, characterized in that The compound having the structure shown in Formula 1 has a mass content of 0.05-10% in the electrolyte; The non-aqueous organic solvent includes at least one of an ether solvent, a nitrile solvent, a carbonate solvent, a carboxylate solvent, and a sulfone solvent. The electrolyte salt includes at least one of a lithium salt, a sodium salt, a potassium salt, a magnesium salt, a zinc salt, and an aluminum salt.
6. The electrolyte according to claim 5, characterized in that The compound having the structure shown in Formula 1 has a mass content of 0.1-5% in the electrolyte; The electrolyte salt is a lithium salt or a sodium salt. and / or the lithium salt comprises at least one of LiPF6, LiBOB, LiDFOB, LiPO2F2, LiBF4, LiSbF6, LiAsF6, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiC(SO2CF3)3, LiN(SO2F)2, LiClO4, LiAlCl4, LiCF3SO3, Li2B 10 Cl 10 , a lithium salt of a lower aliphatic carboxylic acid; The sodium salt includes at least one of sodium perchlorate, sodium hexafluorophosphate, sodium tetrafluoroborate, sodium bisfluorosulfonimide, sodium trifluoromethylsulfonate, and sodium bis-trifluoromethylsulfonimide.
7. The electrolyte of claim 6, wherein, The electrolyte salt is a lithium salt, and the lithium salt has a concentration of 0.1-8 mol / L in the electrolyte. The electrolyte salt is a sodium salt, and the sodium salt has a concentration of 0.1-2 mol / L in the electrolyte.
8. The electrolyte according to any one of claims 4 to 7, characterized in that, The auxiliary additive is selected from at least one of a cyclic carbonate compound, a cyclic sulfate compound, a sulfonic acid lactone compound, a phosphate compound, a borate compound, and a nitrile compound.
9. The electrolyte of claim 8, wherein, The cyclic carbonate compound is selected from at least one of vinylene carbonate, vinyl ethylene carbonate, methylene vinyl carbonate, fluorovinyl carbonate, trifluoromethyl vinyl carbonate, bis-fluorovinyl carbonate, and a compound having a structure shown in Formula 2: In formula 2, R 21 , R 22 , R 23 , R 24 , R 25 , R 26 are each independently selected from one of a hydrogen atom, a halogen atom, a C1-C5 group; and / or the cyclic sulfate compound is selected from at least one of ethylene sulfate, 4-methyl ethylene sulfate, propylene sulfate, and / or the sulfolane compound is selected from at least one of 1,3-propane sultone, 1,4-butane sultone, propenyl-1,3-sultone, The phosphate compound includes a saturated phosphate compound and an unsaturated phosphate compound, wherein the saturated phosphate compound includes tris(trimethylsilyl) phosphate, and the unsaturated phosphate compound includes a compound having a structure shown in Formula 3: in formula 3, R 31 , R 32 , R 32 each independently is selected from a C1-C5 saturated hydrocarbon group, a C1-C5 unsaturated hydrocarbon group, a C1-C5 halogenated hydrocarbon group, or -Si(C m H 2m+1 )3, m is a natural number from 1 to 3, and at least one of the R 31 , the R 32 , the R 33 is an unsaturated hydrocarbon group; The borate compound includes at least one of tris(trimethylsilyl) borate and tris(triethylsilyl) borate. The nitrile compound includes at least one of butanedinitrile, pentanedinitrile, ethylene glycol bis(propionitrile) ether, hexanetristitnitrile, hexanedinitrile, heptanedinitrile, octanedinitrile, nonanedinitrile, and decanedinitrile.
10. A secondary battery comprising a positive electrode, a negative electrode, and an electrolyte, characterized by The electrolyte is the electrolyte according to any one of claims 1 to 9. The secondary battery is selected from a lithium metal battery, a lithium ion battery, a lithium-sulfur battery, a sodium ion battery, a magnesium ion battery, a potassium ion battery, a zinc ion battery, or an aluminum-lithium battery. More preferably, the secondary battery is a lithium ion battery, the positive active material of the secondary battery is selected from lithium-containing sulfides, lithium-containing selenides, lithium-containing halides, LiFe 1-x’ M' x’ PO4, LiMn 2-y’ M y’ O4and LiNi x Co y Mn z M 1-x-y-z O2, wherein M' is selected from at least one of Mn, Mg, Co, Ni, Cu, Zn, Al, Sn, B, Ga, Cr, Sr, V or Ti, M is selected from at least one of Fe, Co, Ni, Mn, Mg, Cu, Zn, Al, Sn, B, Ga, Cr, Sr, V or Ti, and 0 The secondary battery is a sodium ion battery, and the positive active material is selected from at least one of a sodium-containing transition metal oxide, a sodium-containing Prussian material, a sodium-containing phosphate, a sodium-containing sulfate, and a sodium-containing titanate.
Citation Information
Patent Citations
Non-aqueous electrolyte additive and application thereof
CN117186113A
Non-aqueous electrolyte and secondary battery
CN117477027A
Non-aqueous electrolyte additive, non-aqueous electrolyte and secondary battery
CN117558979A
Non-aqueous electrolyte and secondary battery
CN117895075A
Nonaqueous Electrolyte for secondary battery and secondary battery containing the same
KR1020170042079A